Nilai-Nilai Religius Dalam Novel Buya Hamka Karya Ahmad Fuadi - Alfiyah Alfiyah; Linggua Sanjaya Usop; Misnawati Misnawati; Alifiah Nurachmana; Paul Diman (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2023)
The aim of this research is to (1) describe the religious values in the form of belief values in the novel "Buya Hamka" by Ahmad Fuadi, (2) describe the religious values in the form of worship values in the novel "Buya Hamka" by Ahmad Fuadi, (3) describe the religious values in the form of spiritual values in the novel "Buya Hamka" by Ahmad Fuadi, (4) describe the religious values in the form of knowledge values in the novel "Buya Hamka" by Ahmad Fuadi, (5) describe the religious values in the form of practice values in the novel "Buya Hamka" by Ahmad Fuadi. This research is a qualitative descriptive study with a literary sociology approach that focuses on the aspect of religious values. The data source for this research is the novel "Buya Hamka" by Ahmad Fuadi. The data collection technique in this study is done by reading, searching for data, taking notes, and classifying the data. The results of the research on religious values in the novel "Buya Hamka" by Ahmad Fuadi include: (1) religious values in the form of belief values with 11 data, consisting of data about belief in Allah, belief in the Prophet, and belief in predestination, (2) religious values in the form of worship values with 34 data, consisting of data about prayer, fasting, pilgrimage, supplication, remembrance of God, and reading the Qur'an, (3) religious values in the form of spiritual values with 15 data, consisting of data about the feeling of prayers being answered or receiving Allah's help, the feeling of humility during prayer, reliance on Allah, and gratitude, (4) religious values in the form of knowledge values with 7 data, consisting of knowledge about the content of the Qur'an, knowledge about the pillars of Islam, and knowledge about Islamic law, and (5) religious values in the form of practice values with 16 data, consisting of data about willingness to help, giving charity, forgiveness, and patience.